Polymer-Supported (Diacetoxyiodo)benzene Mediated Synthesis of Coumaran-3-ones and cis-3-Hydroxyflavanone dimethylacetals - Kumar, Sunil; Kumar, Devinder (Asian Journal of Chemistry, 2010)
The polymer-supported (diacetoxyiodo)benzene mediated synthesis of coumaran-3-ones and cis-3-hydroxy-flavanone dimethylacetals has been described from 2-hydroxyphenyl alkylketones and 2¢-hydroxychalcones respectively. These are clean oxidation reactions with moderate to high yield.